Bankruptcy Prediction Analysis of PT Garuda Indonesia Compared to Four Airlines Companies in Asia - Fitri, Elda; Darmansyah, Asep; Maya Damayanti, Sylviana (KnE Social Sciences, 2020)
Airline industry is one of the promising industry for investors, it considered a big deal as it predicted to grow rapidly during for the next 20 years. Asia Pacific forecasted as the main player for airline in 2034, which will surpass Europe and North America. SKYTRAX Global Airlines Awards 2018 are announced Garuda Indonesia as one of the top ten best airlines in the world and the Best Cabin Crew in the world. The awards are followed by the other airlines in Asia. Nevertheless, airline industry also known for its volatility business, due to the big amount of operating cost, such as unstable fuel price and the high cost of labor. Those issues affect Indonesia’s best airlines, Garuda Indonesia, experienced loss for the past 5 consecutive years. The purpose of this research is to predict the bankruptcy possibilities of PT. Garuda Indonesia compared to five listed airlines company in Asia, which included as the best airlines in the world. This research will also analyze the relationship of Altman Z”-Score between PT. Garuda Indonesia to other companies by using Coefficient Correlation method. This research will be conducted by using Revised Altman Z” Score for non-manufacturers company which will predict the bankruptcy event for the next two or three years. The sample of this research are Garuda Indonesia (GIAA), Singapore Airlines (SING), THAI Airways (THAI), All Nippon Airways (ANA), and EVA Air (EVA) during the period of 2014-2018. Altman Z”-Score indicates that GIAA, THAI, and EVA predicted to bankrupt, while SING and ANA are predicted to be in the grey zone for the next 2 – 3 years. Keywords: Airline Industry, Bankruptcy, Asia, Garuda Indonesia, Altman Z-Score